A Living River” of Çanakkale Sarıçay Region Examination in the Scope - Zekeriye Gök; Alper Sağlık; Merve Temiz Topsakal (Journal of Advanced Research in Natural and Applied Sciences)
Urban areas are social areas that make it necessary for societies with different cultures to live together. The majority of the world's population lives in urban areas. Especially with the industrial revolution, a large population flow has occurred from rural areas to urban areas. The large and congested population in the cities brings with it a low quality of life. For this reason, people cannot go further than their daily life routines. When we look at the development of civilizations historically, it is seen that the most important source for the sustainability of life is water borders. At the same time, water borders have given identity to the place where it is located as a natural resource such as streams and rivers. The rivers, which are located in the urban area and give an identity to the city, meet the needs of the users along with the protection-use balance, thanks to the recreational uses they offer. Within the scope of the study, a design project that can respond to recreation-al uses has been developed in Sarıçay and its immediate surroundings, which constitute an important ecologi-cal corridor of the city. Visual, natural and cultural environment analyzes were made with SWOT analysis of the area. The aim of the study was to restore the sustainability of Çanakkale Sarıçay and its surroundings to the city and to function it. It is predicted that the study will positively affect the quality of life in the city and the quality of life will increase.